Talking politics online within spaces of popular culture - Graham, Todd (Javnost (Ljubljana), 2010)
Talking politics online is not bound to spaces dedicated to politics, particularly the everyday political talk crucial to the public sphere. The aim of this article is to move beyond such spaces by examining political talk within a space dedicated to popular culture. The purpose is to see whether a reality TV discussion forum provides both the communicative space, content, and style for politics that both extends the public sphere while moving beyond a conventional notion. The central question is whether it fulfils the requirements of rationality and deliberation. The analysis also moves beyond aformal notion by investigating how expressive speech acts interact and influence the more traditional elements of deliberation. The findings indicatethat nearly a quarter of the postings from the Big Brother sample were engaged in political talk, which was often deliberative in nature. It was a communicative space where the use of expressives both facilitated and impeded such talk.
Keywords: javnost; javna sfera; množična kultura; politics; politika; politični nazori; komunikacijska sredstva; svetovni splet; forumi; spletno pisanje